Decreased hepatic enzymes reflect the decreased vitamin B6 levels in Parkinson's disease patients - Kensuke Ikenaka; Yuta Kajiyama; César Aguirre; Chi‐Jing Choong; Seira Taniguchi; Junko Doi; Nan Wang; Takahiro Ajiki; Kotaro Ogawa; Keita Kakuda; Yasuyoshi Kimura; Hideki Mochizuki (Wiley, 2024)
Abstract The study aims to investigate the vitamin B6 levels in Parkinson's disease (PD) patients and their association with liver enzymes and evaluate how much dysregulation is associated with levodopa dose. Furthermore, to evaluate the effect of Opicapone, a catechol‐o‐methyl‐transferase inhibitor, on vitamin B6 levels by monitoring the AST and ALT levels in patients treated with Levodopa-Carbidopa Intestinal Gel Infusion (LCIG). For these aims, serum vitamin B6 levels were measured (PD, n = 72 and controls, n = 31). The vitamin B6 level was compared with the total levodopa dose, clinical parameters, and blood homocysteine, albumin, and hemoglobin levels in PD patients. Correlations between vitamin B6 levels and AST and ALT levels, as well as the ratio ALT/AST, were analyzed. Changes in the AST and ALT levels and ALT/AST were analyzed in the patients treated with LCIG before and after the therapy (n = 24) and in the patients treated with LCIG + Opicapone before and after Opicapone treatment (n = 12). We found vitamin B6 levels were significantly lower in PD patients. Total levodopa dose and albumin levels were independently associated with vitamin B6 levels. Decreased vitamin B6 levels appeared as lower AST and ALT levels and ALT/AS. Treatment with LCIG decreased the AST and ALT levels and ALT/AST. Adjunctive therapy with Opicapone to LCIG ameliorated the decreased ALT and ALT/AST. We conclude that the ALT and ALT/AST can be useful parameters for monitoring vitamin B6 levels and Opicapone can ameliorate the dysregulated vitamin B6 in PD patients.